2011
DOI: 10.1007/s10522-011-9366-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular aging and senescence characteristics of human T-lymphocytes

Abstract: CD28-, CD57+ and KLRG1+ are cell surface markers that have been used to describe senescent T-lymphocytes in humans. However, the relationship among these phenotypes during aging, and their relationship with the concept of in vitro cellular aging have not been well established. Using five-colour flow cytometry, we analyzed peripheral blood T-lymphocytes for their expression of CD28, CD57 and KLRG1 in 11 young (Y) and 11 old (O) apparently healthy human subjects. The proportions of CD28- and CD57+ cells were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 61 publications
1
50
0
Order By: Relevance
“…Although CD28-deficient T cells may contribute to control viral infection, the elevation of CD28 2 CD8 + T cells is generally seen as a significant predictor of immune senescence (5,17,46). Moreover, CD28…”
Section: Cd28mentioning
confidence: 99%
“…Although CD28-deficient T cells may contribute to control viral infection, the elevation of CD28 2 CD8 + T cells is generally seen as a significant predictor of immune senescence (5,17,46). Moreover, CD28…”
Section: Cd28mentioning
confidence: 99%
“…In addition, repeated antigenic challenge through life leads to telomere shortening in lymphocytes (Akbar et al 2004), thus compromising immune memory. T cells from aged donors are also prone to autoimmune reactions as they lose expression of the co-stimulatory molecules CD28 and express markers normally associated with NK cells, such as NKG2D (Alonso-Arias et al 2011) and KLRG1 (Onyema et al 2012), which allow activation by selfantigens.…”
Section: Mdscs Immunosenescence and Ageingmentioning
confidence: 99%
“…In their study the expression of CD57 on T-cells was related to short telomeres and loss of proliferation capacity, possibly linking its presence to senescence (Brenchley et al, 2003). CD28+CD57+ T-cells differ from the more prevalent CD28ÀCD57+ cells, which are known to correspond to a highly differentiated subpopulation with effector function (Onyema et al, 2012). While CD28ÀCD57+ cells have been related to persistent viral infections and an immune risk profile (IRP) (Olsson et al, 2000;Wikby et al, 2002), we have found that CMV seropositivity was not related to the prevalence of CD28+CD57+ cells (Onyema et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…In elderly compared with young persons, we have observed not only a higher prevalence of CD28ÀCD57+ cells, as expected, but also of a small subpopulation that is CD28+CD57+. (Onyema et al, 2012). The attention on CD28+CD57+ cells was first drawn in 2003 by Brenchley et al, who observed in six healthy individuals that 8% of memory CD8+ T cells consisted of the CD28 +CD57+ phenotype.…”
Section: Introductionmentioning
confidence: 99%